HUBUNGAN ANTARA KEMATANGAN EMOSI DENGAN PERILAKU SELF-HARM PADA REMAJA PEREMPUAN - Lutfia Ulfa; Wahyuni Kristinawati (Journal of Innovation Research and Knowledge, 2025)
This study aims to explore the relationship between emotional maturity and self-harm behavior in female adolescents aged 18-21 years. The number of participants in this study was 114, recruited through an online questionnaire. This research employed a quantitative approach with a correlational design. The measurement tools used were the Emotional Maturity Scale and the Self-Harm Inventory (SHI). The results showed a significant negative relationship between emotional maturity and self-harm behavior, with a correlation value of r = -0.803 and significance p < 0.05. This means that the higher the emotional maturity, the lower the self-harm behavior, and conversely, the lower the emotional maturity, the higher the self-harm behavior. Emotional maturity contributed 64% to self-harm behavior. This study is expected to provide a deeper understanding of the importance of emotional maturity in addressing self-harming behavior among female adolescents